2009
DOI: 10.1074/jbc.m109.013961
|View full text |Cite
|
Sign up to set email alerts
|

ID2 (Inhibitor of DNA Binding 2) Is a Rhythmically Expressed Transcriptional Repressor Required for Circadian Clock Output in Mouse Liver

Abstract: Id2 is a helix-loop-helix transcription factor gene expressed in a circadian manner in multiple tissues with a phase-locked relationship with canonical clock genes (1). Our previous studies have identified circadian phenotypes in Id2 null mice, including enhanced photo-entrainment and disruption of activity rhythms, and have demonstrated a potent inhibitory effect of ID proteins upon CLOCK-BMAL1 transactivation of clock gene and clock-controlled gene activity (1). We have now begun to explore the potential rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
63
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(69 citation statements)
references
References 72 publications
6
63
0
Order By: Relevance
“…Transcription of Dbp has been shown to be positively regulated by CLOCK-BMAL1, which binds to an E-box in its promoter (44). Conversely, CLOCK-BMAL1-dependent transcription is antagonized by inhibitor of DNA binding 2 (ID2), which prevents the complex from binding to E-boxes (45,46). In agreement with these findings, we found that among the mRNAs studied, only Id2 mRNA levels were increased in 5/6Nx serum (Fig.…”
Section: Aberrant Id2 Expression Is Associated With Hepatic Dysfunctisupporting
confidence: 80%
“…Transcription of Dbp has been shown to be positively regulated by CLOCK-BMAL1, which binds to an E-box in its promoter (44). Conversely, CLOCK-BMAL1-dependent transcription is antagonized by inhibitor of DNA binding 2 (ID2), which prevents the complex from binding to E-boxes (45,46). In agreement with these findings, we found that among the mRNAs studied, only Id2 mRNA levels were increased in 5/6Nx serum (Fig.…”
Section: Aberrant Id2 Expression Is Associated With Hepatic Dysfunctisupporting
confidence: 80%
“…These proteins include the helix-loop-helix transcription factors, such as Differentially Expressed in Chondorocytes-1 and -2 (DEC1 and DEC2) and Inhibitor of DNA Binding 2 (ID2). These proteins can inhibit CLOCK⅐BMAL1 activities possibly by interfering with formation of the CLOCK⅐BMAL1 complex (27)(28)(29). DEC1 protein was also reported to delay the phases of Per1, Dbp, and Nr1d1 in cells after serum synchronization (30).…”
Section: Discussionmentioning
confidence: 99%
“…ID2 regulates fat metabolism in adipose tissue and liver, and the loss of Id2 leads to decreased adipogenesis, both in vitro and in vivo (18,21). Like ID4, loss of ID2 in vivo severely compromised adipose tissue formation but does not block it completely.…”
Section: Figure 8 Effect Of Hfd On Id4mentioning
confidence: 99%
“…Recently, in vitro studies have shown that ID2 and ID3 may regulate genes expressed during adipocyte differentiation, including adiponectin, hormone-sensitive lipase, and fatty-acid synthase (17,19,20). In addition to its role in adipocyte differentiation, ID2 also is known to contribute to the circadian regulation of lipid metabolism in vivo (21). The expression of another member of this family of proteins, ID4, increases in response to hormone-induced adipocyte differen-tiation, although its role in adipogenesis and adipose tissue formation is unknown (22).…”
mentioning
confidence: 99%